2020
DOI: 10.3390/sym12050803
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Body Constitution Based on TCM Philosophy and Deep Learning

Abstract: There is a growing demand for alternative or complementary medicine in health care disciplines that uses a non-invasive instrument to evaluate the health status of various organs inside the human body. In this regard, we proposed a real-time, non-invasive, and painless technique to assess an individual’s health condition. Our approach is based on the combination of iridology and the philosophy of traditional Chinese medicine (TCM). The iridology chart presents perfect symmetry between the left and right eyes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
6
0
8
Order By: Relevance
“…Yung-Hui Li defines 5 constitutions by the shapes of collarette. When collarette is positioned lesser than 1/3 diameter of iris the constitution is defined as Fire 20 . In this case study, the patient's collarette was shorter than 1/3 diameter of the iris, categorized as 'Fire.'.…”
Section: ⅲ Concl Usi On and Consi Derati Onmentioning
confidence: 99%
“…Yung-Hui Li defines 5 constitutions by the shapes of collarette. When collarette is positioned lesser than 1/3 diameter of iris the constitution is defined as Fire 20 . In this case study, the patient's collarette was shorter than 1/3 diameter of the iris, categorized as 'Fire.'.…”
Section: ⅲ Concl Usi On and Consi Derati Onmentioning
confidence: 99%
“…An iris comprises a large amount of distinctive, constant, and forgery-proof features such as complex textures and explicit structural information for biometric identification [ 5 , 6 ]. In addition to this, iris traits are stable and remain unchanged throughout a person’s lifetime [ 7 ]. Hence, iris texture serves a key role in biometric practices.…”
Section: Introductionmentioning
confidence: 99%
“…A common iris recognition system often consists of the following procedures: Iris image acquisition, iris image pre-processing, iris segmentation, iris feature extraction, and feature matching for identification or authentication [ 1 , 3 , 4 , 6 , 10 ]. In the iris recognition system, iris segmentation is a critical and challenging task because of the unpredictable and irregular shape of the iris [ 4 , 7 ]. In general, iris textures are more visible near the area close to the pupil boundary.…”
Section: Introductionmentioning
confidence: 99%
“…All these domains are dealing with datasets and therefore demand high recognition accuracy with smaller computational complexity. It has been reported that deep learning models have more merits as compared to shallow neural designs [4][5][6][7][8][9]. Differences between DNN and SNN are described in Table 1.…”
Section: Introductionmentioning
confidence: 99%